Clinical Characteristics of Uveitis Patients at Dr. Zainoel Abidin General Hospital Aceh - Samira, Cut Putri; Nilawati, Enny; Islami, Dian; Rosdiana, Eka (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2024)
Introduction: Uveitis is a sight-threatening condition characterized by inflammation in the uveal tract. In Aceh, data on the incidence of uveitis remains unavailable despite numerous reported cases. This study aims to analyze uveitis characteristics in Aceh, Indonesia, and provide information regarding the causes and patterns of inflammation to guide diagnostic and therapeutic approaches. Methods: A retrospective descriptive study was conducted using medical records from Dr. Zainoel Abidin Hospital from uveitis patients between January 2023 and August 2024. Data were analyzed for demographics, clinical presentation, etiology, management, and complications. Results: There were 60 patients with 92 eyes affected with the mean age between 20-44 years. Bilateral involvement occurred in 53.3% of cases with the common chief complaint being blurry vision (53.3%). Tuberculosis was the leading infectious cause (41.3%), while 30.4% of cases were idiopathic. Complications, including cataracts (52%) and glaucoma (12.6%) were prevalent. Conclusion: This study highlights the pattern of uveitis in Aceh, with tuberculosis as the leading cause of infection. Further research into strategies is required to expedite diagnosis and treatment by following local infection trends.